An Optimization Clustering Algorithm Based on Texture Feature Fusion for Color Image Segmentation - Wang, Gaihua; Liu, Yang; Xiong, Caiquan (MDPI, 2015)
We introduce a multi-feature optimization clustering algorithm for color image segmentation. The local binary pattern, the mean of the min-max difference, and the color components are combined as feature vectors to describe the magnitude change of grey value and the contrastive information of neighbor pixels. In clustering stage, it gets the initial clustering center and avoids getting into local optimization by adding mutation operator of genetic algorithm to particle swarm optimization. Compared with well-known methods, the proposed method has an overall better segmentation performance and can segment image more accurately by evaluating the ratio of misclassification.
Keywords: clustering segmentation; local binary pattern; Fuzzy c-means; particle swarm optimization; fi=Tuotantotalous|en=Industrial Management|